2012
DOI: 10.1038/msb.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin measurements reveal contributions of synthesis and decay to steady‐state mRNA levels

Abstract: Histone modification, polymerase binding, mRNA half-life, and miRNA abundance measurements in mouse cells are used to dissect the relative contribution of each to mRNA levels, revealing control primarily at the level of transcription, with minor contributions from post-transcriptional processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
68
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 77 publications
(135 reference statements)
15
68
1
Order By: Relevance
“…These findings indicate that as a general rule, most differences in RNA levels between cell types are accounted for by transcription. This is in agreement with earlier studies showing that gene expression levels can be accurately predicted using only chromatin modifications 36,43 or in addition based on transcriptionfactor binding data 44,45 . For tissue-specific miRNAs, expression is anti-correlated with mRNA expression (corresponding to ∆exon) of the cognate target genes 46,47 .…”
Section: Application Of Eisa To Different Cell Lines and Tissuessupporting
confidence: 82%
See 2 more Smart Citations
“…These findings indicate that as a general rule, most differences in RNA levels between cell types are accounted for by transcription. This is in agreement with earlier studies showing that gene expression levels can be accurately predicted using only chromatin modifications 36,43 or in addition based on transcriptionfactor binding data 44,45 . For tissue-specific miRNAs, expression is anti-correlated with mRNA expression (corresponding to ∆exon) of the cognate target genes 46,47 .…”
Section: Application Of Eisa To Different Cell Lines and Tissuessupporting
confidence: 82%
“…We therefore compared ∆exon -∆intron to changes in log 2 mRNA half-lives 36 from ESCs to terminal neurons ( Fig. 3b) and found that they were significantly correlated ( Fig.…”
Section: Eisa Recovers the Role Of Transcription During Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In various cell types, including DCs, ∼80% of the observed variance in mRNA levels is shaped by transcription rates rather than posttranscriptional regulation (52). Accordingly, our data strongly suggest that IPs shape the transcriptome mainly via regulation of transcription factors and not by affecting mRNA stability.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, outside of the native genomic locus, this sequence recruits the Polycomb machinery in a cell-type-independent manner. The Utf1 locus codes for an established pluripotency factor (29) and is exclusively expressed in ES cells (30). Upon differentiation into neuronal progenitors, Utf1 expression is shut off, accompanied by the gain of H3K27me3 (Fig.…”
Section: Small Functional Prc2 Recruiter Elements Cover Less Than Twomentioning
confidence: 99%